Konsep Penebusan Kristus Dalam Perspektif Teologi Pentakosta - Otieli Harefa; Yudhy Sanjaya; Desetina Harefa; Dewi Lidya Sidabutar; Yusak Hentrias Ferry (Institut Agama Kristen Negeri Kupang, 2021)
This paper is a theological affirmation of the concept of Christ's redemption in Pentecostal theology. This article aims to answer misconceptions about the concept and results of Christ's atoning work on the cross for believers. The method that the authors use to achieve the objectives in this study is to use a descriptive qualitative approach. Through the process of study and analysis, the writer concludes the following points: First, the redemptive work of Christ is a manifestation of God's grace to sinful humans. Second, Christ's death was the act of paying the penalty for human sin. Third, the terms used in redemption affirm that everyone is free from all the wrath of God. Fourth, Christ's redemptive work reconciles man to God, so that every believer has the assurance of eternal life.